An Atlantic cetacean survey using yachtsmen : a pilot study. - Boisseau, Oliver (1999)
In the summer of 1998, yachtsmen sailing from the Caribbean to the Azores were encouraged to take part in an Atlantic cetacean survey. The principle aim of this project was to evaluate the potential of using regular seafarers as sources of data on cetacean distribution. Identification guides and sighting forms were distributed and participants were asked to record any cetacean sightings as well as to conduct routine set-effort watches. A secondary aim of the project was to investigate reports of illegal whaling in the Atlantic. Data collected from the yachtsmen reveal a concentration of sightings along the mid- Atlantic ridge, perhaps corresponding to an increase in productivity in this area. No further reports of whaling activity were made. Although this work only involves a small data set, it illustrates how useful yachtsmen can be in assisting research in otherwise inaccessible regions. Future involvement of yachtsmen in cetacean surveying should be encouraged, as long-term data sets gathered in this way can be invaluable in revealing offshore trends.